Scale dependence of biotic homogenisation by urbanisation: A comparison of urban bird communities between central Argentina and northern Finland - leveau, lucas M; Jokimaki, Jukka; Kaisanlahti-Jokimäki, Marja-Liisa (European Journal of Ecology, 2017)
Recent studies showed contrasting results about the homogenising force of urbanisation on bird communitycomposition at large and regional scales. We studied whether urbanisation promotes the homogenisation ofwintering bird communities and if this varies when comparing towns located within a specific region and townslocated in two different biomes of two countries. We used both similarity indices based on the presence/absencedata and the abundance data in comparing communities. Processes governing bird community dissimilaritybetween urbanisation levels were examined with the partitioning of Sörensen index in species turnover andnestedness. We made bird surveys in town centres and suburban habitats of three cities located in the Pampeanregion of Argentina and in the boreal region of Finland using a single-visit study plot method. Rarefacted speciesrichness did not differ amongst the town centres between the countries, but it was higher in the suburban areasof Argentina than in Finland. At the country-level comparison, we found a higher similarity amongst the towncentres than amongst the suburban areas; whereas at the regional comparison, similarity between town centreswas comparable to the similarity between suburban areas. The use of an abundance-based index produced ahigher similarity between town centre communities of both countries than when using a presence-based index.The dissimilarity between habitats in Argentina was related to nestedness and to species turnover in Finland.Our results indicate that urban-based biotic homogenisation of bird communities is dependent on the scale used,being more evident when comparing cities of different biomes where the same and abundant bird species, suchas sparrows and doves, dominate. At the regional scale, quite a high beta-diversity can still be found within urbanhabitats. Processes of community dissimilarity between urban habitats may differ according to the regionalpool of species, being more related to nestedness toward the tropics.